Effect of Double Ditch Method of Planting on Growth Characteristics of Some Forest Tree Species - Nonhare, B. P.; Chaubey, O. P. (Indian Forester, 1996)
The paper deals with the efficiency of double ditch method of soil working related to the growth of some forest tree species planted at different parts of Panna Forest Division. The response of double ditch method have been recorded in terms of height and collar girth of plants. Tectona grandis, Dendrocalamus strictus and Phyllanthus emblica are the most promising species responded to the double ditch treatment at almost all the sites taken for the study.